Key Insights to Build Strategy for Collaboration as An Organizational Practice -A Case Study of a Professional Service Firm in Thailand - Kamol, Pornpailin; Fernando, Maria Socorro (ABAC ODI JOURNAL Vision. Action. Outcome, 2025)
This study focuses on creating a strategy for building a strategy for collaboration as an organizational practice based on insights on work flexibility, meaningful work, self-transcendence, communication, trust and collaboration. The study aimed to design the a strategy for collaboration as organizational practice based on the common themes from the interviews . This qualitative research utilized questionnaire using the Appreciative Inquiry model for open-ended questionnaire and one-on-one interview with total 15 participants. Content analysis was used to generate themes from interviews which the results showed that the straightforward and honest communication, respect of identity and opinion of others and ability to express opinions, empowerment and delegation, integration of value between work and life, and connection are the common themes in designing strategy for collaboration as an organization practice for this professional firm.